Spatial Convergence in Height in East-Central Europe, 1890-1910 - Marek Brabec; John Komlos (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
We examine spatial convergence in biological well-being in the Habsburg Monarchy circa 1890-1910 on the basis of evidence on the physical stature of 21-year-old recruits disaggregated into 15 districts. We find that the shorter was the population in 1890 the faster its height grew thereafter. Hence, there was convergence in physical stature between the peripheral areas of the monarchy (located in today's Poland/Ukraine, Romania, and Slovakia) and the core (located in today's Austria, Czech Republic, and Hungary). The difference between the trend in the height of the Polish district of Przemysl and the Viennese trend was about 0.9 cm per decade in favor of the former. But the convergence among the core districts themselves was minimal or non-existent, whereas the convergence among the peripheral districts was more pronounced. Hence, spatial convergence took place exclusively within the peripheral areas, and between the peripheral regions and the more developed ones. The pattern is somewhat reminiscent of modern findings on convergence clubs in the global economy. However, the East-Central European pattern was the reverse of this modern finding: heights converged to the levels of the developed regions, but did not converge among the more developed regions themselves.
urn:nbn:de:bvb:19-epub-1358-3
Keywords: D63; I10; J10; N13; N93; O49; 330; spatial convergence; inequality; physical stature; economic growth; biological standard of living; Habsburg Monarchy; anthropometric history; Anthropologie; Gesundheit; Regionales Wachstum; Wirtschaftsgeschichte; Österreich-Ungarn